2009
DOI: 10.1080/08039480903118190
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Norwegian Impact of Event Scale-Revised in a non-clinical sample

Abstract: Background: Despite the widespread use of the Impact of Event Scale to measure post-traumatic stress symptoms, psychometric evaluations of the scale have revealed mixed findings. Aim: The aim of the present study is to provide new empirical evidence and examine the factor structure, reliability, and predictive validity of the Norwegian version of the IES-R. Methods: Posttraumatic stress symptoms were recorded in a student sample (n 0312) 3 weeks after the Southeast Asian tsunami disaster in December 2004. Conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…The psychometric properties of the IES-R have been extensively evaluated and deemed acceptable, with internal consistency within subscales reported to be between .81 and .91, test-retest reliability to be between .52 and .86, and correlation with other measures of posttraumatic stress reactions to be between .53 and .57 [48]. Similar acceptable measures or reliability have been found in a Norwegian non-clinical sample [49]. The internal consistency was high in the present sample (Cronbach's α = .96 and .95 at T 1 and T 2 , respectively).…”
Section: Methodsmentioning
confidence: 90%
“…The psychometric properties of the IES-R have been extensively evaluated and deemed acceptable, with internal consistency within subscales reported to be between .81 and .91, test-retest reliability to be between .52 and .86, and correlation with other measures of posttraumatic stress reactions to be between .53 and .57 [48]. Similar acceptable measures or reliability have been found in a Norwegian non-clinical sample [49]. The internal consistency was high in the present sample (Cronbach's α = .96 and .95 at T 1 and T 2 , respectively).…”
Section: Methodsmentioning
confidence: 90%
“…[11] Arousal measures distress-associated, psycho-physiological activation and is characterized by anger and irritability, a heightened startle response, concentration difficulties, and hypervigilance. However, in contrast to the Weiss and Marmar IES-22-R version, we did not reduce the point level for each item to 0–4 [12], but applied the original 0 -5-point endorsement levels for each item. Thus, the IES applied in our study yields a score range of 0–40 for intrusion (Cronbach’s Alpha 0.807) and avoidance (Cronbach’s Alpha 0.812), and 0–30 for arousal (Cronbach’s Alpha 0.735).…”
Section: Methodsmentioning
confidence: 99%
“…Again, the authors did not test alternative models. Eid et al (2009) tested the factor structure of the IES-R among 312 Norwegian students who had been exposed to media reports of the Tsunami disaster in the weeks following the event. They reported that the original three-factor model exhibited the best fit.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the samples were not sufficiently large to be split into independent subsamples so that findings in one group of participants could be cross-validated in another group. (B) Some of the studies assessed symptoms following stressful, but not necessarily life threatening events so that the nature of the measured symptoms remains unclear (Eid et al, 2009;Olde et al, 2006). (C) The level of symptom severity varied and some studies included a large proportion of participants with no or very few post-traumatic stress symptoms which may have influenced the factor structure (Weiss, 2004).…”
Section: Introductionmentioning
confidence: 99%